Effects of Refining and Petrochemical Effluents on Water Quality and Zooplankton Community in River Rido Kaduna, Nigeria (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2022)
Kaduna Refining and Petrochemical Corporations (KRPC) discharges were studied for a year along the river Rido to determine their impact on water quality and the distribution and abundance of Zooplankton. Physical and chemical parameters were measured following American Public Health Association (APHA) standards for evaluating wastewater. An atomic absorption spectrometer (AAS) was utilized for heavy metal analysis. For this experiment, we used a Plankton net with a 25 m mesh size and a specimen bottle with a 10 cm diameter ring opening to collect zooplankton. Zooplanktons were identified using a standard key and a monograph. Water quality parameters fluctuated, but all were within acceptable ranges except for temperature, conductivity, Total Dissolved Solid, and lead. Zooplanktons were represented in order of abundance by 8 species of protozoa constituting 72.44%, followed by 12 species of Rotifera (10.58%), followed by 13 species of Cladocera 9.55% and then 6 species of Copepoda (7.44%). The planktons showed seasonal variation with high density recorded during the wet season in all the stations. There was a low density of zooplankton in station B, while high density was observed in stations A and D. Also, the low transparency and dissolved oxygen (DO) as well as high mean values of temperature (30.88 oC), chloride (31.88 mg/L), lead (0.099 mg/L), TDS (224.17 mg/L) and conductivity (334.28 µS/cm) observed were above FEPA limits at station B were an indication of pollution and deterioration of water quality. This research revealed that the effluent discharge from KRPC has adverse effects on the zooplankton community and the water quality of river Rido.
Keywords: Petrochemical effluent; KRPC; Physico-chemical parameters; Zooplankton; River Rido Kaduna